Famous composers and their music : extra illustrated edition of 1901 : vol.2 - Thomas, Theodore; Knowles Paine, John; Klauser, Karl (Boston : J.B. Millet Company, 1901)
Bibliotheek Camille Huysmans
Engels
Meerdelige publicatie
Keywords: muziekgeschiedenis